ANALYSIS OF ROBUSTA COFFEE MARKETING CHANNELS IN ULUWAE VILLAGE, EAST LAMBA LEDA DISTRICT, EAST MANGGARAI REGENCY, EAST NUSA TENGGARA PROVINCE - Syukur, Flavianus Pankrasius; Eka Martiningsih, Ni Gst. Ag. Gde; Hanum, Farida (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
Price fluctuations are a significant challenge for coffee farmers when selling their crops. These fluctuations affect the stability of producers' incomes and consumption levels, thereby increasing marketing risks. The method used in this research involves data analysis through observations, interviews with farmer respondents, literature review, and documentation throughout the study. Based on the research conducted with the Ulu Wae Village coffee farmer group, several obstacles were identified. These include rapid and unpredictable weather changes, pests, and diseases that commonly attack coffee plants, such as coffee fruit borers, leaf rust disease, and nematode infestations. One crucial aspect of marketing that needs attention to improve the flow of goods from producers to consumers is marketing efficiency. Improved marketing efficiency can reveal the price differences between what farmers receive and what final consumers pay. Coffee farmers are recommended to market Robusta coffee directly to consumers or form an association that can sell their production directly to consumers. Additionally, agricultural extension officers are expected to continuously provide strategies to manage pests and diseases and to anticipate adverse weather conditions, which are often significant obstacles for farmers cultivating Robusta coffee.